THE ACQUISITION OF TÉH AND MAH BY THE L2 LEARNERS OF SUNDANESE - Eri Kurniawan (LITERA, 2013)
This study examines the second language acquisition of the pragmatic particles téh and mahin L2 Sundanese by Indonesian native speakers. Two groups were compared: (i) a native control group and (ii) an advanced group of Indonesian-speaking adult L2 learners of Sundanese. A pragmatic context-matching felicitousness judgment task wasemployed, following Rothman (2009). A descriptive analysis and a quantitative analysis of the results were conducted, which specifically compared the performance mean score of the L2 learners to that of the native control group. A t-test was used with the alpha setat (0.05) for a 95% confidence level. Assuming the Interface Hypothesis (TsimpliSorace, 2006; Valenzuela, 2006; Sorace, 2007, inter alia), the study presents evidence contrary to the claim that properties mediated at the syntax-pragmatic interface are more difficult to acquire than purely syntactic properties. The advanced L2 learners of Sundanesedemonstrate the native-like L2 knowledge of téh and mah.